Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Restoran Bandoengsche Melk Centrale Kota Bandung - Damayanti, Shinta; Hamali, Arif Yusuf (STIE Ekuitas, 2020)
This research was conducted at Bandoengsche Melk Centrale Restaurant Bandung City, aimed to know the correlation of service quality and customer satisfaction, and also to analyze the influence of service quality to customer satisfaction at Bandoengsche Melk Centrale Restaurant Bandung City. Respondents of this research are 100 selected using incidental sample technique. The method use is descriptive and associative, which tests the influence of dependent and independent variables using Pearson Product Moment correlation analysis, and also done to determine the accuracy of measurement using validity and reliability test. Result of the validity and reliability test of variables X and Y express all valid and reliable. The result showed that service quality at Bandoengsche Melk Centrale Restaurant Bandung City is in the category of good and customer satisfaction is in the category of good. Results showed that there is the correlation of service quality to customer satisfaction at Bandoengsche Melk Centrale Restaurant Bandung City, and based on the interpretation of Pearson Product Moment correlation, this relationship is in the criteria of strong. The result showed that the hypothesis is proved: there is the influence of service quality to customer satisfaction at Bandoengsche Melk Centrale Restaurant Bandung City. Keywords: Service Quality, Customer Satisfaction.